Unity of Curriculum Development Process and Teaching Materials in Islamic Religious Education Subjects - Marwan, Wiranti; Yahiji, Kasim; Ondeng, Syarifuddin; Arif, Muh. (Newinera Publisher, 2023)
This article raises three issues, namely the process of curriculum development in PAI subjects at SDN 25 Limboto, the process of developing teaching materials in PAI subjects at SDN 25 Limboto and the unity of the curriculum development process and teaching materials in PAI subjects. The type of research used is qualitative research. The results showed that the development of curriculum unity and teaching materials is one of the efforts to improve the quality of education in SDN. 25 Limboto, which is done by implementing the 2013 curriculum. The advantage of this curriculum is that teachers can freely choose and determine teaching materials that will be delivered to their students or developed by teachers themselves according to their respective creativity. The development carried out in accordance with the 2013 Curriculum is: Teachers are really responsible for making Learning Implementation Plans (RPP), teachers identify competency standards and basic competencies and teachers.